CRIMINAL LIABILITY FOR CORRUPTION EXTORTION IN OFFICE - Saragih, Diarmin; Pasaribu, Muldri P.J.; Naldo, Rony Andre Christian (Universitas Labuhanbatu, 2025)
In distributing social assistance funds, it is hoped that the Pematangsiantar City Manpower Office will distribute funds to each Joint Business Group (JBG) according to the predetermined amount and without any illegal levies. The legal fact in distribution is that one of the employees of the Pematangsiantar City Manpower Service, without legal standing, committed extortion for the reason of fees. This research discusses criminal liability for corruption, extortion in office. In this regard, this research is focused on examining the application of criminal liability for extortion in office related to the distribution of social assistance funds for JBG in Pematangsiantar City. This research is prescriptive analytical in nature, using normative juridical methods, using a statutory approach, concept approach and case approach. The type of data used is secondary data. The results of the research concluded that the Panel of Judges at the Supreme Court applied criminal liability to defendants of extortion corruption in office related to the distribution of social assistance funds for JBG in Pematangsiantar City based on the provisions of Article 2 of Law Number 20 of 2001, and not based on the provisions of Article 12 letter (e) Law Number 20 of 2001.Keywords: Liability; Corruption; Extortion.